A rewilding agenda for Europe: creating a system of experimental reserves - Jepson, P (Wiley, 2015)
In the context of aging European conservation institutions rewilding has emerged as a popular and scientific expression of new directions in ecology and conservation management associated with the restoration of ecosystem function through reassembly of trophic levels involving the reintroduction of large mammals. It introduces a radical new natural archetype that evokes a positive environmentalism. The Oostvaardersplassen experiment in the Netherlands demonstrates the agency of rewilding for nature development and engaging diverse publics in debates on what is natural and the future of conservation policy. If conservation is to retain its cultural and policy visibility and influence in a 21st century multicultural Europe, our conservation institutions and the natures we value must adapt. In this forum I frame rewilding as an asset for institutional adaptation that is being constrained by substantive institutional and societal resistance. I argue the need for strategic investment in a European network of experimental rewilding sites. These would bring rewilding into densely populated areas, develop the science and practice of ecosystem restoration, and promote public debate on nature conservation futures. The ‘Fitness check’ of European nature conservation legislation mandated in 2014 is a case of high politics. In this situation, compromise and negotiation is inevitable and the environmental lobby needs something to advocate as well as defend. A rewilding agenda could fulfill this need.